Efficacy of combined hypo-fractionated radiotherapy and anti-PD-1 monotherapy in difficult-to-treat advanced melanoma patients. (3rd July 2018) - Roger, Anissa; Finet, Adeline; Boru, Blandine; Beauchet, Alain; Mazeron, Jean-Jacques; Otzmeguine, Yves; Blom, Astrid; Longvert, Christine; de Maleissye, Marie-Florence; Fort, Magali; Funck-Brentano, Elisa; Saiag, Philippe
ABSTRACT: Information on the role of radiotherapy in anti-PD-1 monoclonal antibody-treated melanoma patients is limited. We report on a prospective cohort of advanced melanoma patients treated simultaneously with radiotherapy and anti-PD-1 therapy between 01/01/15 and 30/06/16. Tumor evaluations (RECIST 1.1) were performed every 3 months on radiated and non-radiated lesions. Twenty-five advanced melanoma patients (64% AJCC stage IV M1c, 64% on second-line treatment or more, 60% with elevated LDH serum levels) were included. Radiotherapy was performed early (median: 24 days) after the first anti-PD-1 dose in 15 patients with rapidly progressing symptomatic lesion(s) or later (median: 5.4 months) in 10 patients with progressive disease (PD) despite PD-1 blockade. Radiotherapy was limited to one organ in 24 patients and consisted mainly of hypo-fractioned radiotherapy (median dose 26 Gy in 3–5 fractions, 17 patients) or brain radiosurgery (5 patients). Median follow-up after first anti-PD-1 dose was 16.9 m (range 2.7-27.4), with 44% of patients alive at last follow-up. For radiated lesions, rates of complete (CR), partial (PR) responses, stable disease (SD) or PD were 24%, 12%, 24%, and 32%, respectively. For non-radiated lesions, rates of CR, PR, SD, and PD were 20%, 19%, 12%, and 40%, respectively. Responses achieved after radiotherapy for radiated and non-radiated areas were correlated (Pearson correlation r : 0.89, P <0.0001) suggesting an abscopal effect. Five patients with CR remained disease-free after discontinuation of anti-PD-1 for a median of 9.5 months. No unusual adverse event was recorded. Hypo-fractionated radiotherapy may enhance efficacy of anti-PD1 therapy in difficult-to-treat patients. Controlled studies are needed.